The Implementation of the Principle of Justice in the Profit-Sharing System of Oil Palm Plantations from the Perspective of Islamic Economic Law: (A Study in Kampung Tanjung Tiga) - Juwita Olivia; Adista (EL-IQTISHAD: Journal of Economics, Business and Sharia Studies, 2026)
This study aims to analyze the profit-sharing system practices in oil palm plantations in Kampung Tanjung Tiga, examine their compliance with Islamic economic law principles, and formulate solutions to establish a more just and transparent system. This research employs a qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using descriptive qualitative methods. The findings reveal that the profit-sharing practices are commonly implemented; however, they are largely based on informal verbal agreements without written contracts, lack transparency in yield calculations, and reflect unequal bargaining positions between landowners and managers. These conditions indicate that the practices have not fully complied with the principles of justice (al-‘adl), contractual clarity, and the avoidance of gharar (uncertainty) in Islamic economic law. Therefore, improvements are necessary, including the establishment of written agreements, enhanced transparency, strengthening farmer institutions, and increasing public literacy in Islamic economic law. This study is expected to contribute to the development of more equitable and sustainable Islamic economic practices.